PERENCANAAN PENDIDIKAN DI SEKOLAH DASAR - Rina Yuliana (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
The goals of Social and economic development can be achieved through the optimal educational planning. Unfortunately, the develovment of education  especially for primary education was not in accordance with the procedures of educational planning  that should be designed. Most of the education at the primary levels  were developed with the vision, mission, and goals clearly  by paying attention to the interests of society and the ability of people who designed a comprehensive, accurate, precise, and efficient based on the fact. The aim of the paper is  to explain the concept of primary education planning, along with the process. Moreover, it was presented the strategic issues that occur in primary education.The strategic issues of empirical facts which were related to the primary education for the children can be implemented through policies that can be established with a comprehensive educational planning process in accordance with the needs of socio-economic environment. There are three strategies were explained in this paper that can be developed for the equity of education , they are: Revisit priorities, multistandard Curriculum and Evaluation System that Empower the education system. Keywords: Education plannning, Equities of primary Education